“We have to save him”: a qualitative study on care transition decisions in Ontario’s long-term care settings during the COVID-19 pandemic - Sarah Carbone; Whitney Berta; Susan Law; Kerry Kuluski (BMC Geriatrics, 2023)
Abstract Background The COVID-19 pandemic has contributed to a global crisis in long-term care (LTC) with devastating consequences for residents, families and health professionals. In Ontario, Canada the severity of this crisis has prompted some care partners to move residents home with them for the duration or a portion of the pandemic. This type of care transition, from LTC to home care, was highly unusual pre-pandemic and arguably suboptimal for adults with complex needs. This paper presents the findings of a qualitative study to better understand how residents, care partners, and health professionals made care transition decisions in Ontario’s LTC settings during the pandemic. Methods Semi-structured interviews were conducted with 32 residents, care partners and health professionals who considered, supported or pursued a care transition in a LTC setting in Ontario during the pandemic. Crisis Decision Theory was used to structure the analysis. Results The results highlighted significant individual and group differences in how participants assessed the severity of the crisis and evaluated response options. Key factors that had an impact on decision trajectories included the individuals’ emotional responses to the pandemic, personal identities and available resources. Conclusions The findings from this study offer novel important insights regarding how individuals and groups perceive and respond to crisis events.